Urinary tract infections are common and have an impact on performance in elite wheelchair athletes: a cross-sectional study of self-reported data - Anneke Hertig-Godeschalk; Claudio Perret; Jörg Krebs; Fabian Ammann (Swiss Medical Weekly)
STUDY AIMS: Wheelchair athletes may be at risk of urinary tract infections, especially those with spinal cord injury. A urinary tract infection can lead to a loss of training hours and reduced performance in athletes. We assessed the self-reported occurrence of urinary tract infections and the impact of urinary tract infections on training and performance in elite wheelchair athletes. We also evaluated the prophylactic measures used, as reported by the athletes.